Comparative evaluation of Lactobacillus strains with different adhesion ability on growth performance and immunomodulatory activity in broiler chickens - CAO, LI; WU, XIAO-HONG; WANG, XUE-YANG; LI, GE-GE (The Indian Journal of Animal Sciences, 2019)
The study was designed to assess the effect of 2 Lactobacillus strains (Lactobacillus kefiri 1.3207 and Lactobacillus plantarum 1.2567) with different adherence ability on growth performance and immunomodulatory activity in broiler. The BW and FCR were higher in L. kefiri 1.3207 and L. plantarum 1.2567 groups compared to control group at 42 days of age, and BW of broilers in L. kefiri 1.3207 group was significantly higher than that in L. plantarum 1.2567 group. IgA and IgG contents and the spleen and bursa of Fabricius indices in significantly increased in the L. kefiri 1.3207 group, but not in the L. plantarum 1.2567-treated group. L. kefiri 1.3207 had more significant effect on growth performance, plasma IgA and IgG levels and immune organs indices because it had better adhesion ability.